2018
DOI: 10.1002/acn3.514
|View full text |Cite
|
Sign up to set email alerts
|

The interrelation between clinical presentation and neurophysiology of posthypoxic myoclonus

Abstract: ObjectivePosthypoxic myoclonus (PHM) in the first few days after resuscitation can be divided clinically into generalized and focal (uni‐ and multifocal) subtypes. The former is associated with a subcortical origin and poor prognosis in patients with postanoxic encephalopathy (PAE), and the latter with a cortical origin and better prognosis. However, use of PHM as prognosticator in PAE is hampered by the modest objectivity in its clinical assessment. Therefore, we aimed to obtain the anatomical origin of PHM w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is generally taught that massive, axial jerks might be associated with highly malignant EEG patterns, whereas brief, mostly multifocal jerks do not always herald a poor prognosis; however, the clinical-neurophysiological association of myoclonus appears unreliable. 16,17 EEG showing underlying continuous, reactive patterns suggests a treatable post-anoxic myoclonus, most likely representing early forms of Lance-Adams syndrome. 6,14,18 This syndrome might be incapacitating initially, but responds to treatment and is compatible with a good long-term outcome.…”
Section: Reviewmentioning
confidence: 99%
“…It is generally taught that massive, axial jerks might be associated with highly malignant EEG patterns, whereas brief, mostly multifocal jerks do not always herald a poor prognosis; however, the clinical-neurophysiological association of myoclonus appears unreliable. 16,17 EEG showing underlying continuous, reactive patterns suggests a treatable post-anoxic myoclonus, most likely representing early forms of Lance-Adams syndrome. 6,14,18 This syndrome might be incapacitating initially, but responds to treatment and is compatible with a good long-term outcome.…”
Section: Reviewmentioning
confidence: 99%
“…Power spectrum was estimated based on 1‐second segments with overlap of 50%, according to Welch's method. CMC was considered positive if its values exceeded a 95% confidence level for at least four consecutive frequency bins, 24 within a 10–40 Hz range 19 . The 95% confidence limit was calculated according to the following formula: 1−(0.05) 1/(L−1) , where L is the number of analyzed segments 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Some have also proposed that defining SSEP amplitudes are key in defining acute PHM. Giant SSEPs, which can signify cortical myoclonus, may predict a better outcome, 12,28 although the cortical and subcortical dichotomy for prognosis is controversial, as will be discussed later. Giant SSEPs are not specific for cortical myoclonus and can be seen in other neurological disorders.…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 99%
“…12,27 Therefore, the dichotomy between acute and chronic PHM in the literature is not sufficient to differentiate cases with good or poor prognosis and thus in defining PHM for prognostic and management decisions. 8,23,28 The differentiation between "malignant," which implies a poor outcome, from less malignant or "benign" acute PHM is crucial given these prognostic implications because acute PHM itself may lead to the withdrawal of life-sustaining therapy. It has been suggested that clinical features and ancillary neurophysiological testing hold the key to better defining outcomes when acute PHM is present.…”
mentioning
confidence: 99%
See 1 more Smart Citation